2021
DOI: 10.3390/ani11113020
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Mixed Organic Acids Improves Growth Performance, Meat Quality, Gut Morphology and Volatile Fatty Acids of Broiler Chicken

Abstract: Background: Organic acid as a green feed additive is increasingly favoured by enterprises and scholars, but little emphasis has been placed on the effect of organic acids on broiler meat quality. Methods: A total of 192 male chicks (one-day-old, weighted 48.40 ± 0.64 g) were selected to investigate the effect of mixed organic acids (MOA) on growth performance, meat quality as well as fatty acids profile. Chicks were randomly allocated to three treatments with eight replicates and eight chicks per replicate, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…It was confirmed again in this study that dietary supplementation with the organic acid, BFMA, improved the growth performance of broilers, including increasing ADFI, ADG, and BW, and decreasing FCR and DCR. Besides the benefits on growth performance, supplementation of mixed organic acids increased pH 24 h of the breast and thigh muscles, and the redness in thigh meat was also improved [ 36 ]. Organic acids prevent meat quality deterioration without leaving any chemical residues [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed again in this study that dietary supplementation with the organic acid, BFMA, improved the growth performance of broilers, including increasing ADFI, ADG, and BW, and decreasing FCR and DCR. Besides the benefits on growth performance, supplementation of mixed organic acids increased pH 24 h of the breast and thigh muscles, and the redness in thigh meat was also improved [ 36 ]. Organic acids prevent meat quality deterioration without leaving any chemical residues [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of fatty acids on shelf life depends on the proportion of unsaturated fatty acids (UFAs) [57]. Moreover, the higher the UFA concentrations are, the faster the fatty acid rate spoilage, and fatty acid products could accelerate the oxidation of myoglobin to methemoglobin, resulting in decreased meat quality in broiler chickens [58]. Some natural antioxidants can be used to delay the oxidation of fat and myoglobin in meat products [59].…”
Section: Discussionmentioning
confidence: 99%
“…Galli et al [ 190 ] showed that the supplementation of organic acids (blends of formic, phosphoric, lactic, acetic, butyric, and propionic acids; 0.75 to 3 g/kg of feed) reduced yellowness and improved the antioxidant status in the breast meat of broiler chickens. Ma et al [ 191 ] showed that the supplementation of blends of formic acid, ammonium formate, acetic acid, propionic acid, and lactic acid (3 to 6 g/kg of feed) increased the meat pH and increased the ratio of polyunsaturated to saturated fatty acids in the breast meat. The supplementation of organic acids has the potential to alter the meat quality of broiler chickens.…”
Section: Effects Of Nutritional Interventions On the Meat Quality Of ...mentioning
confidence: 99%